Proportional Human Rights Protection in Democratic Transitions: Perlindungan HAM Proporsional dalam Transisi Demokrasi - Hetharia, Melkias (Rechtsidee, 2026)
General Background Human rights protection is a constitutional foundation of democratic rule of law and a safeguard against authoritarian regression. Specific Background In democratic transitions, states must balance political stability, transitional justice, and human rights protection. Knowledge Gap Previous studies have not sufficiently compared how different legal systems shape institutional and judicial roles in protecting human rights during democratic transition. Aims This study analyzes human rights protection in transitional democracies through a normative comparative legal approach between Indonesia and the United States. Results The findings show that proportionality is the main standard for lawful rights limitation through legality, legitimate aim, suitability, necessity, and balancing tests. Non-derogable rights, including the right to life, freedom from torture, and freedom of religion, must remain absolutely protected. Indonesia’s civil law system places courts within statutory frameworks, while the United States’ common law system gives courts broader authority through judicial review. Novelty This study integrates proportionality and transitional justice in comparing civil law and common law models. Implications The findings emphasize institutional strengthening, judicial accountability, and state-society collaboration. Highlights: Proportionality guides lawful limitation of rights. Non-derogable rights remain absolutely protected. Legal systems shape judicial authority differently. Keywords: Human rights protection, democratic transition, transitional justice, proportionality, comparative law